Інституційні межі контрольно-наглядової діяльності за підприємницькою діяльністю в Україні - Воюцька, В. С.; Voiutska, V. S. (Наше право. - 2022. - № 3. - С. 234-240, 2022)
З’ясовано зміст інституційних меж контрольно-наглядової діяльності за підприємницькою діяльністю в сучасній Україні. Виокремлено та окреслено основні інституційні межі контрольно-наглядової діяльності за підприємницькою діяльністю. Визначено основні типи та види суб’єктів контрольно-наглядової діяльності у контексті контролю і нагляду за підприємницькою діяльністю в Україні.

The objective of this article is to clarify the current scholarly consensus on the institutional constraints governing control and supervisory activities over entrepreneurship in Ukraine. These constraints are part of a wider set of legal restrictions and prohibitions that must be duly considered in the planning, organization, and execution of such activities. Importantly, these constraints delineate the scope of authorized entities that are permitted, under existing legal statutes, to undertake roles in control and supervision at various governance levels – local, regional, national, and even international. Included within these institutional constraints is the stipulation that there must be no overlap in control and supervisory functions among distinct public administrative bodies; that is, multiple entities should not engage in the oversight of identical matters. Another cornerstone of this institutional framework is the mandate for both the state and civil society to safeguard the autonomy and independence of the bodies tasked with these oversight roles. Notwithstanding this autonomy, there exists a tiered structure of public governance, which serves to instill a degree of legal certainty into these activities and aids in pinpointing the entities accountable for the enactment of particular control and supervisory measures. The effi cacy of abiding by these institutional limitations is contingent upon a comprehensive understanding by supervisory and control bodies of both the variety of entities involved in such activities and the systemic structure governing them. In terms of their administrative and legal characteristics, entities involved in the control and supervisory activities concerning business operations in Ukraine can be categorized into distinct types. Utilizing this classifi catory criterion, one can delineate two primary kinds of entities: fi rst, those affi liated with public service, encompassing both the institutional bodies and the offi cials therein; and second, actors from civil society. Drawing upon the typology proposed for entities engaged in control and supervisory activities over entrepreneurial undertakings in Ukraine, one can identify four distinct categories. The fi rst encompasses entities with generalist competencies, notably local state administrations, and local self-governance bodies. The second category consists of sector-specifi c entities, including but not limited to ministries such as the Ministry of Finance of Ukraine, the Ministry of Environmental Protection and Natural Resources of Ukraine, and the Ministry of Internal Affairs of Ukraine, as well as other central executive organs like the State Customs Service of Ukraine, the State Tax Service of Ukraine, and the National Health Service of Ukraine. The third category is made up of entities vested with specialized competencies, either directly linked to entrepreneurial activities or manifested within this domain. The State Regulatory Service of Ukraine serves as the principal entity in this classifi cation. This category also includes specialized agencies focused on discrete aspects of business behavior, for instance, the National AntiCorruption Bureau of Ukraine, the National Agency for the Prevention of Corruption, the Bureau of Economic Security of Ukraine, and the State Service of Ukraine on Labor Issues, among others. The fourth and fi nal category is constituted by civil society entities that undertake control and supervisory roles within the entrepreneurial fi eld. In summation, the fi ndings of this investigation advocate for the establishment and sustained operation of a centralized register in Ukraine, designed to catalog entities responsible for the oversight and regulation of business activities.

Выяснено содержание институциональных границ контрольно-надзорной деятельности за предпринимательской деятельностью в современной Украине. Выделены и очерчены основные институциональные границы контрольно-надзорной деятельности за предпринимательской деятельностью. Определены основные типы и виды субъектов контрольно-надзорной деятельности в контексте контроля и надзора за предпринимательской деятельностью в Украине.
Institutional boundaries of control and supervisory activities over business activities in Ukraine
Keywords: громадський контроль; законність; інституційні межі; контроль; контрольно-наглядова діяльність; нагляд; підприємницька діяльність; публічне адміністрування; business activity; control and supervisory activities; control; institutional boundaries; legality; public administration; public control; supervision; общественный контроль; законность; институциональные границы; контрольно-надзорная деятельность; предпринимательская деятельность; публичное администрирование